2019
DOI: 10.1186/s40658-018-0240-9
|View full text |Cite
|
Sign up to set email alerts
|

Real-time data-driven motion correction in PET

Abstract: PET imaging has been, and continues to be, an evolving diagnostic technology. In recent years, the modernizing digital landscape has opened new opportunities for data-driven innovation. One such facet has been data-driven motion correction (DDMC) in PET. As both research and industry propel this technology forward, we can recognize prospects and opportunities for further development. The concept of clinical practicality is supported by DDMC approaches—it is what sets them apart from traditional hardware-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…First clinical studies already have demonstrated that DDG methods are equivalent to BG methods in terms of image quality and lesion quantification (14,15); accordingly, vendors have started incorporating DDG algorithms into their PET systems (17). However, more studies are needed to ensure that DDG works well in a wide range of applications, radiotracers, and scanning modes (31).…”
Section: Discussionmentioning
confidence: 99%
“…First clinical studies already have demonstrated that DDG methods are equivalent to BG methods in terms of image quality and lesion quantification (14,15); accordingly, vendors have started incorporating DDG algorithms into their PET systems (17). However, more studies are needed to ensure that DDG works well in a wide range of applications, radiotracers, and scanning modes (31).…”
Section: Discussionmentioning
confidence: 99%
“…4 ). This problem affects particularly small lesions in the upper abdomen, such as accessory spleens, IPAS and pNET 47 50 .…”
Section: Discussionmentioning
confidence: 99%
“…DL methods have been used for improving PET image quality, reducing noise [54], removing streak artifacts from CT [55], and developing novel techniques for tomographic image reconstruction based on a reduced amount of acquired data. Other promising applications are a generation of synthetic images, such as synthetic CT from MRI [56], virtual contrast-enhanced images [57], and rigid/deformable intramodal and multimodal image registration [58], and extraction of the respiratory signal [21] that could be used for breathing motion compensation of images [59].…”
Section: Imagingmentioning
confidence: 99%